2019
DOI: 10.22146/ijc.33140
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Genetic Manipulation Improved <i>Saccharomycopsis fibuligera</i> α-Amylase Secretion by <i>Pichia pastoris</i>

Abstract: This study assessed the combinations of genetic manipulation; signal peptide modification, gene dosage increment and co-expression of folding component, to increase Saccharomycopsis fibuligera R64 α-amylase (Sfamy) secretion in Pichia pastoris. Sfamy native signal peptide was replaced with modified signal peptide which contained 15 amino acid of mouse salivary α-amylase signal peptide fused to the pro-region of the signal peptide of Saccharomyces cerevisiae α-mating factor (α-MF). Increase in gene dosage was i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…In addition to single-copy integration, multi-copy integration is generally demanded for high-level expression of the target proteins. The pPIC series of vectors are commonly used integrative vectors in P. pastoris [ [23] , [24] , [25] , [26] ], which enable the screening of the multi-copy integration strains under high concentration of antibiotics, a mechanism known as post-transformation amplification [ [27] , [28] , [29] , [30] ]. In addition to the formation of tandem repeats via post-transformation amplification, multi-copy strains can be constructed by integrating into the repetitive sequences of the P. pastoris genome, such as the ribosomal DNA (rDNA) sequences [ 13 ].…”
Section: Synthetic Biology Toolkit For P Pastorismentioning
confidence: 99%
“…In addition to single-copy integration, multi-copy integration is generally demanded for high-level expression of the target proteins. The pPIC series of vectors are commonly used integrative vectors in P. pastoris [ [23] , [24] , [25] , [26] ], which enable the screening of the multi-copy integration strains under high concentration of antibiotics, a mechanism known as post-transformation amplification [ [27] , [28] , [29] , [30] ]. In addition to the formation of tandem repeats via post-transformation amplification, multi-copy strains can be constructed by integrating into the repetitive sequences of the P. pastoris genome, such as the ribosomal DNA (rDNA) sequences [ 13 ].…”
Section: Synthetic Biology Toolkit For P Pastorismentioning
confidence: 99%
“…Confirmation of rHSA sequence by using the dideoxy Sanger method using universal primers for pD912 shows 100% homology to HSA sequence (Supplement material 2). The expression of HSA by P. pastoris was carried out extracellularly by using methanol as an inducer (Gaffar et al, 2019).…”
Section: Generation Of Recombinant P Pastoris Harboring Rhsamentioning
confidence: 99%
“…Pichia pastoris demonstrates a remarkably attractive host for HSA production due to several benefits of this expression system. Pichia pastoris is a widely used host for recombinant protein expression due to the fact that it is easy to manipulate, its genetic structure is stable, it has a high cell density when growing in an inexpensive basal salt medium, it has strong inducible alcohol oxidase 1 (AOX1) promoter, it has the ability to perform posttranslational modification, and it has a high capacity of secretory expression and low endogenous protein secretion (Ahmad et al, 2014;Baghban et al, 2018;Gaffar et al, 2019). Recently, Zhu et al (2018) have reported the production of rHSA in P. pastoris GS115 hosts in a shake flask and fermenter culture yielded 1.6 and 8.86 g/l, respectively.…”
Section: Introductionmentioning
confidence: 99%